Carpe diem—Time to transition from empiric to precision medicine in kidney transplantation. Issue 7 (30th April 2018) - Wiebe, Chris; Ho, Julie; Gibson, Ian W.; Rush, David N.; Nickerson, Peter W.
Abstract : The current immunosuppressive pipeline in kidney transplantation is limited. In part, this is due to excellent one‐year allograft outcomes with the current standard of care (ie, calcineurin inhibitor in combination with anti‐proliferative agents). Despite this success, a recent Federal government–sponsored systematic review has identified gaps/limits in the evidence of what constitutes optimal calcineurin inhibitor use in the short‐ and long‐term. Moreover, recent empiric approaches to minimize/withdraw/convert from calcineurin inhibitors have come with the price of increased alloreactivity. As the time horizon to replace calcineurin inhibitors on a global scale may be distant, the transplant community should seize the opportunity to develop ways to personalize calcineurin inhibitor immunosuppression to the individual—transitioning from empiricism to precision. The authors argue in this viewpoint that the path to precision will require measures capable of detecting subclinical alloreactivity to define adequacy of immunosuppression, as well as novel genetic analytics to accurately define alloimmune risk at the individual level—both approaches will require validation in clinical trials. Abstract : The path to precision medicine in transplantation will require modern alloimmune risk quantification and monitoring for immunosuppression adequacy.